Fluorescence Lifetime Correlation Spectroscopy (FLCS): concepts, applications and outlook - Kapusta, Peter; Macháň, Radek; Benda, Aleš; Hof, Martin (International journal of molecular sciences, 2012)
Fluorescence Lifetime Correlation Spectroscopy (FLCS) is a variant of fluorescence correlation spectroscopy (FCS), which uses differences in fluorescence intensity decays to separate contributions of different fluorophore populations to FCS signal. Besides which, FLCS is a powerful tool to improve quality of FCS data by removing noise and distortion caused by scattered excitation light, detector thermal noise and detector afterpulsing. We are providing an overview of, to our knowledge, all published applications of FLCS. Although these are not numerous so far, they illustrate possibilities for the technique and the research topics in which FLCS has the potential to become widespread. Furthermore, we are addressing some questions which may be asked by a beginner user of FLCS. The last part of the text reviews other techniques closely related to FLCS. The generalization of the idea of FLCS paves the way for further promising application of the principle of statistical filtering of signals. Specifically, the idea of fluorescence spectral correlation spectroscopy is here outlined.
Keywords: fluorescenční barviva; liposomy; Photons; teoretické modely; Fluorescent Dyes; Models, Theoretical; Spectrometry, Fluorescence; difuze; fluorescenční spektrometrie; Liposomes; fotony; Diffusion